A Review of Brand Anthropomorphism : Analysis of Trends and Research - Ubgade, Pritha Nasery; Joshi, Sujata (Prabandhan: Indian Journal of Management, 2022)
In recent years, it could be observed that the anthropomorphism of products and brands offered a unique transformative opportunity for marketing managers. Researchers found that when products or brands were anthropomorphized (i.e., when human-like features were given to non-human entities), they acquired a positive consumer attitude, which ultimately increased purchase intentions. As a result, the available literature on brand anthropomorphism matured over the period. This study tried to map the research done in brand anthropomorphism across the globe from 2000 to 2021 in various Scopus-indexed journals, using tools such as Advanced Excel, VOS Viewer, and Biblioshiny—a bibliometric analysis tool. The results suggested that The Computers in Human Behaviour was the leading journal that published the most articles related to brand anthropomorphism. Also, the study indicated that the authors and journals from the United States contributed the most in this area. The study was relevant from the managerial perspective as many companies were anthropomorphizing their products and brands, thus strengthening the consumer-brand relationship. In conclusion, this study intended to provide valuable insights to scholars and marketing managers about the present and future scope of research in this area.